(untitled) (Revista Contexto & Saúde, 2026)
Objective: To investigate the prevalence of eating disorders in patients with type 1 diabetes mellitus and the correlation with depression, anxiety, and stress. Method: Cross-sectional observational study. The sample consisted of 111 patients with type 1 diabetes mellitus, assessed using structured questionnaires, including the Eating and Weight Patterns Questionnaire-5, the Sick Control One Stone Fat Food questionnaire, and the Depression, Anxiety, and Stress Scale. Variables were analyzed using descriptive statistics. Associations between categorical variables were tested using the chi-square test (including Monte Carlo simulation when necessary), and quantitative variables were analyzed using Student’s t-test. Variables with p < 0.20 in the univariate analysis were included in a multivariate logistic regression model using the backward method, with p < 0.05 considered statistically significant. Results: The results revealed that 37.8% of participants presented eating disorders according to the Sick Control One Stone Fat Food test, whereas the Eating and Weight Patterns Questionnaire-5 identified a prevalence of 2.7%. In addition, a significant association was observed between the presence of eating disorders and elevated body mass index, as well as between eating disorders and depression. The analysis of mental health symptoms showed prevalences of 22.5% for depression, 21.6% for anxiety, and 13.5% for stress among the patients. Conclusion: The findings indicate that patients with type 1 diabetes mellitus are at increased risk for eating disorders, particularly when associated with higher body mass index and symptoms of depression. These results reinforce the need for early screening strategies and integrated follow-up care that includes mental health.